The problem of “culture” in the process of intercultural understanding - Andreana Marchi; E. Doyle McCarthy (Ilha do Desterro)
The problem of “culture” in the process of intercultural understanding is one of the most discussed issues among scholars today. Anthropologists, linguists, literary critics, and philosophers, just to name a few, study this issue in a problem-based and research format. Culture and cultural understanding are hereby presented by demonstrating studies and observations of two cultural anthropologists, R. H. Robbins and Clifford Geertz, a literary critic, Lionel Trilling, and C. S. Lewis, a famous writer of both fiction and non-fiction. My intention here is to answer the question: how to describe and analyze a culture that is so different from the perspective of our own? In this sense, language and discourse are also analyzed in this paper as part of culture and can indicate some of our own moral perspectives and judgments on others’ cultures.